Neoadjuvant immunotherapy in nonsmall cell lung cancer. Issue 1 (January 2021) - Pall, Georg
Abstract : Purpose of review: Immune-checkpoint inhibitors have improved treatment outcomes for metastatic nonsmall cell lung cancer (NSCLC). Whether this therapeutic potential might also translate into survival gains in earlier stages is an area of active research. Based on preclinical rationale the neoadjuvant administration of immunotherapeutic agents is of special interest. This review is intended to summarize the existing background, published early clinical evidence, and provide perspective on future developments regarding neoadjuvant immunotherapy in NSCLC. Recent findings: Preclinical data and early clinical trials suggest promising efficacy of immune-checkpoint inhibitors in early-stage NSCLC when administered in a neoadjuvant manner. Compared to historical controls, the rates of pathologic and radiographic regression seem to be improved, in particular when immunotherapy is combined with standard platinum-based chemotherapy. These favorable treatment effects are accompanied by a moderate toxicity profile without impairing surgical outcomes. Several phase III trials are underway to provide definitive evidence. Summary: Neoadjuvant immunotherapy has the potential to substantially improve outcomes in early-stage NSCLC and therefore to change daily clinical practice in the near future.